2004
DOI: 10.3200/jach.53.1.28-34
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Exercise, and Sedentary Behavior in College Students

Abstract: The authors examined the relationship between physical activity, exercise, and sedentary behaviors in 493 college students who were enrolled in 10 conditioning activity classes and had completed questionnaires at the beginning of the course. They analyzed sedentary activities and indicators of participation in exercise and physical activity by demographic variables. Surveyed men reported greater participation in physical activity and exercise than did women, and they also spent more time watching television/vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
234
5
14

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(273 citation statements)
references
References 4 publications
20
234
5
14
Order By: Relevance
“…Previous research has suggested that there are gender differences in regard to both exercise behaviour and alcohol consumption, with males being more likely to exercise (e.g., Buckworth & Nigg, 2004) and to consume more alcohol (e.g., Wilsnack, Wilsnack, Kristjanson, Vogeltanz-Holm & Gmel, 2009)) than females.…”
Section: Generalisability Of Research Findingsmentioning
confidence: 99%
“…Previous research has suggested that there are gender differences in regard to both exercise behaviour and alcohol consumption, with males being more likely to exercise (e.g., Buckworth & Nigg, 2004) and to consume more alcohol (e.g., Wilsnack, Wilsnack, Kristjanson, Vogeltanz-Holm & Gmel, 2009)) than females.…”
Section: Generalisability Of Research Findingsmentioning
confidence: 99%
“…The percentages almost double in college (19% of males and 26% of females). Buckworth and Nigg's [10] finding that college students spend almost 30 hours a week engaged in sedentary activity support these data. While rates of physical activity steadily decline in college [33] it is true that habits formed during college tend to be fairly well sustained.…”
Section: Introductionmentioning
confidence: 76%
“…Calfas and colleagues [11] reported that 84.7% of college seniors who exercised regularly were active a decade later. Unfortunately, the opposite appears to be true as well; 80% of inactive college seniors continue their sedentary behavioral patterns after college [10,33,43,50]. Given that engaging in physical activity leads to a host of well-established physiological and psychological benefits [5,18,46,48,49] and that lack of physical activity is a modifiable risk factor of chronic disease understanding how to enhance the college students' experience in physical activity is critical.…”
Section: Introductionmentioning
confidence: 99%
“…For sedentary behavior one question addressed how many hours the student watched TV or played video games on an average day (Buckworth and Nigg 2004). Validity of this item has shown a small negative correlation in PA with children (Nigg 2005 Participants reported how many servings of fruits and how many servings of vegetables they ate each day.…”
Section: Methodsmentioning
confidence: 99%